Grain yield and termite damage in rice by compaction on the furrow and seed treatment - Pinheiro, Veneraldo; Stone, Luís Fernando; Barrigossi, José Alexandre Freitas; Nascente, Adriano Stephan (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to determine the effects of soil compaction pressure on the sowing furrow and of seed treatments with insecticides on grain yield and on termite damage in upland rice plants under no-tillage, in the Center West region of Brazil. Three experiments were carried out, consisting of five seed treatments combined with three (first experiment) or four (second and third experiments) compaction pressures in a randomized complete block design, in a factorial arrangement. The seed treatments were: T0, without treatment; T1, imidacloprid+thiodicarb; T2, thiamethoxam; T3, carbofuran; and T4, fipronil+pyraclostrobin+thiophanate-methyl. The compaction pressures applied were: 25, 42, and 268 kPa, in the first experiment; and these same pressures plus 126 kPa in the second and third experiments. Seed treatment was effective in increasing rice grain yield, from 1,753 to 4,141 kg ha‑1, especially in the lowest compaction pressure of 25 kPa. Soil compaction around 180 kPa in the sowing furrow results in higher rice grain yield and in fewer stems killed by termites. The use of soil compaction on the sowing furrow with seed treatment significantly increases rice grain yield under a no-tillage system.